Empowering Muslim Women through Digital Da’wah: A Case Study of Hijabers Community Medan - Effendy, Ellyta; Abdullah, Abdullah; Rubino, Rubino (MUHARRIK: Jurnal Dakwah dan Sosial, 2024)
This study investigates the strategies and effectiveness of digital da'wah implemented by the Hijabers Community Medan, emphasizing women's empowerment through new media. Recognizing the urgency of understanding innovative religious communication methods in the digital age, particularly those targeting Muslim women, this research adopts a qualitative case study approach. Employing purposive sampling, eight key informants including community leaders, da'wah experts, and media specialists were selected to provide diverse perspectives. Primary data were gathered through semi-structured in-depth interviews, participatory observations conducted over six months, and content analysis focusing explicitly on the community's Instagram posts from the past year. Data validity was ensured through methodological triangulation, an audit trail documenting the research process, and rich, contextual descriptions. The analytical framework integrated Henry Jenkins' new media theory, Paulo Freire's empowerment theory, and Everett Rogers' diffusion of innovation theory to explore the dynamics of digital participation, empowerment, and innovation adoption within religious communities. Data analysis followed the Miles, Huberman, and Saldana model, employing NVivo software for systematic coding and thematic categorization. Findings reveal that the Hijabers Community Medan employs diverse digital strategies such as persuasive storytelling, visually engaging microblogs, and structured messaging via social platforms, fostering active community participation and enhancing women's religious identity. Despite these successes, challenges emerged including internal communication conflicts, inconsistent member engagement, and external misconceptions regarding their ideological stance. Critically, this study identifies the need for deeper empirical evaluation of digital strategies’ impact. The Inclusive Digital Da'wah Model of Hijabers Medan (DID-HM) proposed from these findings requires further validation through extended quantitative and comparative research to ascertain its broader applicability and effectiveness.